2014
DOI: 10.1371/journal.pone.0093662
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of MicroRNAs in Normal Equine Tissues by Next Generation Sequencing

Abstract: The role of microRNAs (miRNAs) as a post-transcriptional gene regulator has been elucidated in a broad range of organisms including domestic animals. Characterization of miRNAs in normal tissues is an important step to investigate the functions of miRNAs in various physiological and pathological conditions. Using Illumina Next Generation Sequencing (NGS) technology, we identified a total of 292 known and 329 novel miRNAs in normal horse tissues including skeletal muscle, colon and liver. Distinct sets of miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 47 publications
6
42
0
Order By: Relevance
“…From five most abundantly expressed novel putative miRNA reported in equine plasma by Lee et al [37], only one miRNA was identified in our study in bone and blood tissues with a mature sequenced shorter by three nucleotides from 5’ end. From the 329 novel miRNAs reported by Kim et al [9] only 11 had exactly the same mature sequence as novel miRNAs reported here. From the 896 putative novel miRNAs included in the microarrays used by Mach et al [32] only two had exactly the same mature sequence and further 24 had few nucleotides shorter mature sequence compared to the miRNAs identified here (Additional file 4: Table S3).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…From five most abundantly expressed novel putative miRNA reported in equine plasma by Lee et al [37], only one miRNA was identified in our study in bone and blood tissues with a mature sequenced shorter by three nucleotides from 5’ end. From the 329 novel miRNAs reported by Kim et al [9] only 11 had exactly the same mature sequence as novel miRNAs reported here. From the 896 putative novel miRNAs included in the microarrays used by Mach et al [32] only two had exactly the same mature sequence and further 24 had few nucleotides shorter mature sequence compared to the miRNAs identified here (Additional file 4: Table S3).…”
Section: Discussionsupporting
confidence: 68%
“…Nonetheless, from the 166 tissue-specific known equine miRNAs reported in liver, colon or muscles, a total of 132 were expressed in our study and 105 of them were expressed at >10 cpm on average in at least one group. Interestingly, 21 miRNAs reported as tissue-specific in Kim et al [9] were also expressed in all groups studied here, at > 10 cpm on average. From the 31 liver-specific miRNAs reported by Kim et al [9], only one was supported by our study with our definition of tissue specificity (eca-miR-135a).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Novel miRNAs have been mapped to chromosomes excluding chromosomes 29 and 31. Moreover, detailed analysis revealed that equine miRNA are distributed across chromosomes in 51 clusters, with 160 miRNAs corresponding to 55 % of known miRNAs (Kim et al 2014). …”
Section: Gene Expression Profiling and Annotation Of Novel Genes In Tmentioning
confidence: 99%